1988
DOI: 10.1073/pnas.85.21.7867
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+-linked increase in coupled cAMP synthesis and hydrolysis is an early event in cholinergic and beta-adrenergic stimulation of parotid secretion.

Abstract: The dynamics and compartmental characteristics of cAMP metabolism were examined by 180 labeling of cellular adenine nucleotide a phosphoryls in rat parotid gland stimulated to secrete with .8-adrenergic and cholinergic agents.The secretory response occurred in association with a rapidly increased rate ofcAMP hydrolysis apparently coordinated with an equivalent increase in the rate of cAMP synthesis, since the cellular concentration of cAMP remained unchanged. The magnitude of this metabolic response was equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…First, a coordinated regulation of PKA activity by adenylyl cyclase and cAMP-PDE activities could influence the steady-state concentration of cAMP required for full activation of PKA in cells in a manner independent of absolute cAMP levels. 52 In support of this model, Deeg et al 53 demonstrated that parotid gland amylase secretion was stimulated by a coordinated increase in both adenylyl cyclase and PDE activity such that the cells seemed to respond to an increase in cAMP metabolism even though the levels of cAMP did not change. In addition, subcellular colocalization of selected PDE and PKA isoforms may allow for a coordinated regulation of function.…”
Section: Discussionmentioning
confidence: 89%
“…First, a coordinated regulation of PKA activity by adenylyl cyclase and cAMP-PDE activities could influence the steady-state concentration of cAMP required for full activation of PKA in cells in a manner independent of absolute cAMP levels. 52 In support of this model, Deeg et al 53 demonstrated that parotid gland amylase secretion was stimulated by a coordinated increase in both adenylyl cyclase and PDE activity such that the cells seemed to respond to an increase in cAMP metabolism even though the levels of cAMP did not change. In addition, subcellular colocalization of selected PDE and PKA isoforms may allow for a coordinated regulation of function.…”
Section: Discussionmentioning
confidence: 89%
“…Secondly, it is possible that an increase in the metabolic cycling of cAMP (which is revealed under conditions of phosphodiesterase inhibition) is capable of activating this enzyme in the absence of a measurable increase in the total cellular level of cAMP. Such a metabolic cycling of cAMP has been reported to mediate early amylase secretion in the rat parotid gland [18]. Thirdly, since this assay measures net substrate phosphorylation, it is possible that mechanisms independent of cAMP-dependent protein kinase activity may influence total substrate phosphorylation.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic administration of ISP-induced cellular hypertrophy and hyperplasia of acinar cells in the parotid glands (Yashiro et al, 1987). Similarly, P-adrenergic agonist stimulated a-amylase secretion in the rat parotid gland, which was accompanied by intracellular accumulation of CAMP (Ito et al, 1981;Deeg et al, 1988;Baldys-Waligorska et al, 1987;Snowdowne et al, 1989;McKinney et al, 1989). In a human submandibular tumor cell line, ISP was shown to stimulate cAMP production (Marmary et al, 1989).…”
Section: Discussionmentioning
confidence: 98%